Socially resilient mobility planning: Main challenges and design implications - Oliver Weberg; Jesper Lund; Vaike Fors; Andrea Resmini (Transportation Research Interdisciplinary Perspectives)
As mobility systems evolve, their design must enable people to adapt to disruptions in their daily lives and routines, making social resilience a vital yet underexplored focus. This is why this study investigates the question: What are the challenges when designing for social resilience in local mobility services? Semi-structured interviews with seven mobility experts revealed the need for a shift from prioritising organizational resources to enhancing social capacity, emphasising individuals’ strengths and established routines. The main challenges for urban planners and developers to achieve this were identified through a lack of guidelines for incorporating social sustainability into mobility planning, that in turn renders difficulties in employing qualitative methods tailored for enabling citizen and stakeholder engagement, as well as developing deeper understandings of local, social life. These findings are illustrated in this article through five design implications, each highlighting strategies to integrate social resilience into mobility systems, ensuring they are responsive and supportive of the communities they serve.